Helping Small Water Utilities Become Bankable - Elvas, Leila H. (World Bank, Washington, DC, 2012)
Small water utilities with fewer than 5,000 connections comprise over 90 percent of the known network systems in urban areas in the Philippines. By developing their capacity to improve their performance, they have more chances of being creditworthy and bankable so that they can finance investments for expansion and service improvements. The Small Water Utilities Improvement and Financing (SWIF) Project of the World Bank's Water and Sanitation Program (WSP) in the Philippines worked with 11 small water utilities to help them do strategic planning and prepare performance improvement plans and to prepare cost recovery tariffs as well as project proposals that can be submitted to a bank. They can easily reorganize their investment plans to suit available financing. This smart lesson shares lessons learned by the project team in helping these small water utilities become bankable, including making sure everyone gets training, ring-fencing the accounts of water operations, and helping close the gap between what utilities want and what banks want.